2013
DOI: 10.7243/2049-7962-2-1
|View full text |Cite
|
Sign up to set email alerts
|

High SIRT1 expression and low DBC1 expression are associated with poor prognosis in colorectal cancer

Abstract: Background: SIRT1 deacetylates various cellular proteins in addition to histones and functions as an either tumor-promoter or tumor-suppressor. The participation of SIRT1 in colorectal cancer onset and progression remains controversial. SIRT1 activity is regulated among the others by deleted in breast cancer 1 (DBC1). We asked if the expression of the SIRT1-inhibitor DBC1 affects contribution of SIRT1 to colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…This result is in agreement with previous findings by Cha et al, 32 Stenzinger et al, 33 and Kikuchi et al, 34 who reported that SIRT1 expression was associated with poor survival in various human cancers. SIRT1 is known to deacetylate the major tumor regulators such as P53, FOXO3a, and HIC1, 35 thereby allowing defective DNA to bypass the cell cycle, escape apoptosis, and lead to tumor formation.…”
Section: Discussionsupporting
confidence: 95%
“…This result is in agreement with previous findings by Cha et al, 32 Stenzinger et al, 33 and Kikuchi et al, 34 who reported that SIRT1 expression was associated with poor survival in various human cancers. SIRT1 is known to deacetylate the major tumor regulators such as P53, FOXO3a, and HIC1, 35 thereby allowing defective DNA to bypass the cell cycle, escape apoptosis, and lead to tumor formation.…”
Section: Discussionsupporting
confidence: 95%
“…Also, the expression and function of DBC1 within various malignancies were not yet confirmed. And, the cutoff scores for DBC1 expression in present studies are significant incongruity 4,22 ,36-37. Despite there was no critical error in our data extraction and statistical analysis, the phenomena described above may lead to differences in results.…”
Section: Discussionmentioning
confidence: 53%
“…If we simply assume that SIRT1 is a tumor promoter, whereas DBC1 a tumor suppressor counteracting SIRT1, the relative abundance of SIRT1 to that of DBC1 should be elevated in cancers. However, we previously reported that the above simple assumption was not valid in colon cancer [ 30 ]. Excessive SIRT1 activity due to low DBC1 expression might be unfavorable for cancer cell growth.…”
Section: Discussionmentioning
confidence: 99%